An Advanced Energy System Using a Small Fast Reactor as an Energy Source - Yasuyoshi Kato; Y. Muto; Takao Ishizuka; N. Nikitin; M. Utamura (Indonesian Journal of Physics, 2008)
An advanced energy system has been proposed that involves a supercritical carbon dioxide gas turbine fast reactor (S-CO2 FR) as a dispersed energy source, a new waste-heat recovery system from the FR, and a bioconversion system using the recovered waste heat. The FR with S-CO2 gas turbine achieves higher cycle efficiency than conventional sodium-cooled FRs with steam turbines, eliminating problems of conventional FRs related to safety, plant maintenance, and construction costs. The S-CO2 FR consumes minor actinide elements produced in light water reactors as fuel, thereby reducing long-lived radioactive wastes and environmental loads imparted by long-term geological disposal. The recovered waste heat is used for methane and methanol production through fermentation of human and animal wastes in cities and farms. The methane and methanol are easily transported and can accommodate demand changes; they are useful as fuel of fuel cells, automobiles, and gas turbine power plants. The total energy utilization efficiency in electricity and heat is estimated to be higher than 85%, contributing to saving of energy resources and reduction of greenhouse-gas emissions. Consumption of the waste products of cities and farms for production of methane and methanol fosters a recycling society. Compact and high-performance microchannel heat exchangers are used in the S-CO2 FR, the new waste-heat recovery system and the fermentation system.